2008
DOI: 10.1016/j.jri.2007.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity of a multi-component recombinant human acrosomal protein vaccine in female Macaca fascicularis

Abstract: A vaccine formula comprised of five recombinant human intra-acrosomal sperm proteins was innoculated into female monkeys to test whether specific antibodies to each component immunogen could be elicited in sera and whether antibodies elicited by the vaccine affected in vitro fertilization. Acrosomal proteins, ESP, SLLP-1, SAMP 32, SP-10 and SAMP 14, were expressed with his-tags, purified by nickel affinity chromatography and adsorbed to aluminum hydroxide. Five female cynomolgus monkeys were inoculated intramu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 33 publications
(35 reference statements)
0
17
0
Order By: Relevance
“…In order to achieve 100% contraceptive effect, the proteins on different domains of sperm need to be targeted, as every domain is responsible for a function leading to successful fertilization. It has been suggested that immunization with a multivalent vaccine containing multiple sperm antigens can generate a greater anti-fertility effect than a single sperm antigen (Kurth et al 2008). As part of our effort to identify putative protein targets for the development of posttesticular male contraceptives, we exploited combinatorial approach of SI followed by proteomics to delineate potential targets from different sperm domains.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to achieve 100% contraceptive effect, the proteins on different domains of sperm need to be targeted, as every domain is responsible for a function leading to successful fertilization. It has been suggested that immunization with a multivalent vaccine containing multiple sperm antigens can generate a greater anti-fertility effect than a single sperm antigen (Kurth et al 2008). As part of our effort to identify putative protein targets for the development of posttesticular male contraceptives, we exploited combinatorial approach of SI followed by proteomics to delineate potential targets from different sperm domains.…”
Section: Discussionmentioning
confidence: 99%
“…For a target to be considered suitable for a vaccine approach, immunogenicity is very crucial and therefore separate studies have been specially designed by investigators to establish immunogenicity of otherwise well-characterized proteins such as ESP, SLIP-1, SPACA1, ACRV1, and SPACA4 (Kurth et al 2008. Our approach was unique as it identified only those proteins, which are immunogenic, ruling out the need for a separate study to establish the immunogenicity of the identified proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Various health organizations and pharmaceutical companies actively continue to pursue research towards new contraceptive approaches [2]. Presently, based on the variable antigens (Ags) existing in the male reproductive system, researchers have developed many antibodies (Abs) or vaccines for contraception, such as Abs to SP-10 expressed in the testis that could interfere with the union of sperm and ovum [3]. The sperm-specific protein, Izumo, a member of immunoglobulin superfamily (IgSF) which is located on the sperm stimulates hamster to secrete high titer of Abs both in the genital tract and serum and further decreases their reproductive capability [4].…”
Section: Introductionmentioning
confidence: 99%
“…The idea to use sperm proteins as contraceptives arose from studies reporting infertility in 70% of the vasectomized men and 30% of the infertile couple due of the presence antisperm antibodies. 11,12 With the objective to identify more targets, we recently reported several novel epididymis-specific proteins using the combinatorial approach. 5 Decline of fertility post-immunization with sperm proteins has been reported.…”
Section: Resultsmentioning
confidence: 99%